2018 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2018
DOI: 10.1109/iros.2018.8593450
|View full text |Cite
|
Sign up to set email alerts
|

Associative Skill Memory Models

Abstract: Associative Skill Memories (ASMs) were formulated to encode stereotypical movements along with their stereotypical sensory events to increase the robustness of underlying dynamic movement primitives (DMPs) against noisy perception and perturbations. In ASMs, the stored sensory trajectories, such as the haptic and tactile measurements, are used to compute how much a perturbed movement deviates from the desired one, and to correct the movement if possible. In our work, we extend ASMs: rather than using stored si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…As an example, if the end-effector had carried a heavy object that significantly changed the measured forces when the robot was required to be compliant, the weight of the objects should have been used as the parameter to the model. In a previous study, 31 we showed the advantage of using the weight of the object as the parameter to the force-feedback model in an object pushing task. While we had used PHMMs to encode the force-feedback trajectory, the robot was provided only one trajectory to learn: the movement of the end-effector along a straight line while pushing an object.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, if the end-effector had carried a heavy object that significantly changed the measured forces when the robot was required to be compliant, the weight of the objects should have been used as the parameter to the model. In a previous study, 31 we showed the advantage of using the weight of the object as the parameter to the force-feedback model in an object pushing task. While we had used PHMMs to encode the force-feedback trajectory, the robot was provided only one trajectory to learn: the movement of the end-effector along a straight line while pushing an object.…”
Section: Resultsmentioning
confidence: 99%
“…We already studied such correcting actions in ref. [31] where our system exploited those models to correct the perturbed movements during executions with the aim of generalizing to novel configurations.…”
Section: Compliance In Parametric Dmpsmentioning
confidence: 99%
“…12,[19][20][21] Others have integrated learning meta and shape parameters, either hierarchically 9 or in parallel. [21][22][23] While RL Motion adaptation using manifold of task and movement primitive parameters 3 indeed facilitates acquiring new skills, its use for adaptation during runtime has several limitations. The continuous parameter space along with the high dimensionality of typical robotic motor-learning problems lead to long learning epochs.…”
Section: Related Workmentioning
confidence: 99%
“…Rueckert et al 28 suggest using hierarchical Bayesian models for estimating both meta and shape parameters for probabilistic movement primitives. Ugur and Girgin 20,21 suggest learning parametric hidden Markov models from multiple demonstrations for encoding relations between shape parameters and environment properties. Probabilistic movement primitives facilitate encoding optimal behaviors in stochastic systems, yet when deterministic system behavior (i.e., completely predictable operation) is required, they are less suitable.…”
Section: Related Workmentioning
confidence: 99%
“…Memorized force and tactile profiles have already been successfully utilized in modulating learned DMPs in difficult manipulation tasks that contain high degrees of noise in perception such as grasping and in-hand manipulation of objects from incorrect positions or flipping boxes using chopsticks [17]. HMMs were used to learn multi-modal models from temperature, pressure and fingertip information for exploratory object classification tasks [7]; and PHMMs were used to learn haptic feedback trajectory models to adapt actions in response to external perturbations [10,21]. Deep networks [8] were used to learn multi-modal models from different sensory information such as temperature, pressure, fingertip, contacts, proprioception, and speech; however these models were used only to categorize the sensory data without any effect on action execution.…”
Section: Related Workmentioning
confidence: 99%